PENGARUH PEMASARAN DIGITAL TERHADAP BRAND IMAGE CAFÉ JANJI JIWA - Gagih Pradini; Anisa Putri Kusumaningrum; Glenn Abdillah Wibisono (Jurnal Ilmiah Wahana Pendidikan, 2026)
Kemampuan Understanding brand image in the digital era is a crucial strategy for gaining a competitive advantage. Digital marketing conducted via electronic devices or the internet enables consumers to seek information about products they intend to purchase and access testimonials from other consumers regarding their experiences with those products. This study aims to determine the impact of digital marketing on the brand image of Café Janji Jiwa. The growing coffee-drinking trend among tourists compels local coffee shops to innovate continuously; thus, this research is expected to provide appropriate strategic insights for Café Janji Jiwa. The variables employed in this study are Digital Marketing (X) as the independent variable and Brand Image (Y) as the dependent variable. A quantitative research approach was adopted, utilizing simple linear regression analysis based on data from 100 Café Janji Jiwa consumers in Jakarta. The findings indicate that digital marketing does not have a positive and significant effect on the brand image of Café Janji Jiwa.